THE EFFECT OF TRUST, PERCEIVED EASE OF USE, AND PERCEIVED RISK ON CONTINUANCE USE OF GOPAY: THE EFFECT OF TRUST, PERCEIVED EASE OF USE, AND PERCEIVED RISK ON CONTINUANCE USE OF GOPAY - Rahayu, Shinta Sri; Kusumastuti, Sri Yani (PENANOMICS: International Journal of Economics, 2025)
Drawing on the Technology Acceptance Model (TAM) and the Expectation–Confirmation Model (ECM), this study investigates the effects of perceived ease of use, trust, and perceived risk on the continuance usage of the GoPay digital wallet. A quantitative research design was employed using a survey of 391 GoPay users in Indonesia. Data were collected through a structured Likert-scale questionnaire and analyzed using Structural Equation Modeling (SEM) to examine the proposed relationships. The findings indicate that perceived ease of use has a positive and significant effect on continuance usage, supporting TAM’s proposition that usability enhances users’ post-adoption behavior. Trust also exhibits a positive and significant influence on continuance usage, highlighting the role of transaction security, system reliability, and personal data protection in reinforcing users’ confirmation of expectations, as emphasized in ECM. In contrast, perceived risk does not significantly affect continuance usage, suggesting that potential risks are perceived as manageable and do not outweigh the perceived benefits of continued use. Overall, the results confirm that perceived ease of use and trust are the primary determinants of digital wallet continuance usage, while the integrated model explains users’ post-adoption behavior effectively. This study contributes to the fintech literature by extending TAM and ECM to the context of digital wallet services and offers managerial insights for strengthening user retention through usability and trust-enhancing strategies.